f(e^x-1)=3x-2,求f(x)
2个回答
令 u=e^x-1 则 x=ln(1+u)
所以f(e^x-1)=f(u) = 3ln(1+u)-2
所以f(x)=3ln(1+x)-2
相关问题
f(1+x)-2f(1-x)=3e^x求f(x)
设f(x)=e^(-x) *ln(2-x) + (1+3x^2)^(1/2),求f'(1)
设f(x)=[e^x+e^(-x)]/2,g(x)=[e^x-e^(-x)]/2,计算f(1)g(3)+g(1)f(3)
两个复合函数的问题设f(e^x+1)=e^2x+e^x+1,求f(x)设f(x+1/x)=x^2+1/x^2,求f(1/
设f(x)=e^-x*ln(2-x)+根号(1+3x^2),求f'(1)
跪求f(x)=(根号下x^2-3x-4)/x 1y=e^(x^2)f[x^(e^2)]
设f(2x+1)=e^x,求f'(x),f'(lnx)
设函数f(x)=x^2e^(x-1)-1/3x^3-x^2 X∈R 1求函数y=f(x)的单调区间 2求f(x)在【-1
第一题,知道f(x)=3 +x^2+tan(πx/2),-1<x<1,求f'(3) 第二题 知道f(x)=3+x+e^x
设当x≤0时,f(x)=1+x^2,x>0时,f(x)=e^(-x),求∫(1,3)f(x-2)dx